Age and gender distribution of community periodontal index of treatment needs - a record-based study - CHELLAPPA, LALITHA RANI; LEELAVATHI, L.; JAYASHRI, P. (The journal of contemporary issues in business and government, 2021)
Gingivitis and periodontitis are two main periodontal diseases in which gingivitis is reversible and periodontitis is irreversible. Pocket depth and loss of attachment can distinguish gingivitis and periodontitis. Their distribution with age and gender and association is still a controversy. Aim of the study was to analyse the distribution of community periodontal health and its treatment needs among patients attending a private dental college in Chennai.CPITN index was used to measure the CPI scores and treatment needs of individual indexed teeth.This study included all CPITN index patient records from 18- 80 years old who visited from August 2019- March 2020 and a total of 112 records were reviewed. Descriptive statistics and chi square tests were used for statistical analysis.Gender distribution of the records showed that among 112 records 72.32% were males and 29.68 % were females. Bleeding (38.24%) was the most prevalent CPI score among the study population. Improvement of oral hygiene and scaling (44.04%) was commonly found treatment needs. Significant association was found between age and treatment needs of most of the index teeth . There was no significant association found between gender and CPI score or Treatment Needs of the index teeth. In the age group of 18 - 35 years, bleeding was found to be more prevalent; calculus was found to be more prevalent in the age groups 36-50 years and 51-80 years. Improvement of personal oral hygiene and scaling was the most prevalent treatment needs among all the age groups. Calculus was observed more prevalent among males and bleeding was common among females. Improvement of personal oral hygiene and scaling was the most prevalent treatment needs among both males and females.